Honey exposure stimulates wound repair of human dermal fibroblasts - Elia Ranzato (Burns & Trauma, 2013)
Honey is widely used for treating burns, ulcers and wounds, but the mechanisms of action are poorly known and the product is mainly used as an antimicrobial. We have examined here the wound healing properties of honey on human fibroblasts, using an in vitro scratch wound healing model. Three kinds of widely used monofloral honeys were used, viz. acacia (Robinia pseudacacia), buckwheat (Fagopyrum sp.), and manuka (Leptospermum scoparium). Data displayed an increased wound healing activity in fibroblasts, but with different efficiency and mechanisms of action among honeys. The effects of acacia and buckwheat emerged in both scratch wound and chemotaxis assays, while the effect of manuka was significant but lower. The use of inhibitors indicated on the whole an essential role of cytosolic calcium, an important role of ERK and p38, and a secondary role of PI3K. Acacia and buckwheat, but not manuka, induced significant increases in the release of interleukin-4 (IL-4), IL-6, and IL-8, indicating a correlation between interleukin upregulation and wound closure efficiency. This is consistent with our previous findings suggesting a higher ability of acacia and buckwheat to activate keratinocyte reepithelialization, with respect to manuka honey. In conclusion, our data indicate that acacia and buckwheat honeys are particularly efficient in facilitating fibroblast wound closure activities, suggesting new therapeutic possibilities for this natural product.